Effects of high-intensity interval training on the VO2 response during severe exercise - Duffield, R.; Edge, J.; Bishop, D. (Journal of Science and Medicine in Sport, 2006)
This study examined the effect of high-intensity interval training on the VO2 response during severe, constant-load exercise. Prior to, and following training, 10 females (VO2peak 37.4 ± 6.0 mL kg-1 min-1) performed a graded exercise test to determine VO2peak and lactate threshold (LT) and a 6 min cycle test (CT) at the pre-training VO2peak intensity. Training involved high-intensity intervals (2 min work, 1 min rest) performed 3× week for 8 weeks. Breath-by-breath data from 0 to 6 min during the CT were smoothed using 5 s averages and fit to a bi-exponential model starting from 20 s. Training resulted in significant improvements in VO2max (2.34 ± 0.37-2.78 ± 0.30 L min-1), power at VO2max (170 ± 26-204 ± 25 W) and power at LT (113 ± 17-136 ± 20 W) (p < 0.05). Following training, the VO2 response showed a significant increase in the amplitude of the primary phase (A1) (1396 ± 103-1695 ± 100 mL min-1; p < 0.05) and end-exercise VO2 ( VO2ee ), with no difference (p > 0.05) in the time constants of either phase or the amplitude of the slow component (318 ± 67-380 ± 48 mL; p = 0.15). In conjunction, accumulated oxygen deficit (AOD) (43.7 ± 9.8-17.2 ± 2.8 mL O2 eq kg-1) and anaerobic contribution to the CT (19.4 ± 4.4-7.2± 1.2%) were significantly reduced. In contrast to previous moderate-intensity research, a high-intensity interval training program increased A1 and VO2ee for the same absolute exercise intensity, decreasing the AOD during a severe-intensity CT.